THE ROLE AND SIGNIFICANCE OF EXPERT OPINION AS A MEANS OF PROOF (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This thesis provides a comprehensive analysis of the role and significance of expert opinion as a means of proof within the framework of criminal procedural legislation. It examines the legal nature of expert opinion, the procedure for its appointment and conduct, its place in the system of evidence, and its interrelation with other means of proof. Particular attention is given to the criteria for evaluating expert opinion, including reliability, objectivity, scientific validity, and compliance with procedural requirements.The thesis substantiates that expert opinion plays a decisive role in resolving criminal cases, especially in establishing circumstances that require specialized knowledge. Its features as both incriminating and exculpatory evidence, its role in shaping the internal conviction of the court, and its importance in ensuring fair judgments are highlighted. In addition, the study analyzes the development trends and current issues of the forensic examination institution based on existing criminal procedural legislation, judicial practice, and scholarly approaches.As a result, it is concluded that expert opinion is an essential means of proof in criminal proceedings, contributing to the establishment of truth, strengthening the evidentiary basis, and ensuring the legality and validity of judicial decisions.